Genetic variability in symbiotic nitrogen fixation within and between provenances of two Casuarina species using the 15Nlabelling methods - Sanginga, N.; Bowen, G.D.; Danso, S.K.A. (Elsevier, 1990)
Differences in the nitrogen-fixing abilities of provenances of Casuarina equisetifolia and C. cunninghamiana were assessed in pot experiments. Three methods, the 15N isotope dilution, the A value and total N difference were used to measure N2 fixed. There was a good agreement between the A value and isotope dilution methods for measuring N2 fixed. The total N difference method gave unreliable values, with large coefficients of variation. There were significant differences in the proportions and amounts of N2 fixed in the two Casuarina species with C. equisetifolia deriving on the average 63% or 45 mg N plant−1 from atmospheric N2 fixation, compared to 43% or 22 mg N plant−1 by C. cunninghamiana. Nitrogen fixation also varied substantially within provenances of each species with the percentage of N derived from atmospheric N2fixation (% Ndfa) ranging from 14 to 76% for the C. cunninghamianaprovenances and from 25 to 75% within C. equisetifolia (equivalent to 2–25 mg N plant−1 and 4–29 mg N plant−1 for the two species, respectively). Growth of C. equisetifolia and C. cunninghamianaincreased with either inoculation with Frankia or N fertilizer addition, but marked differences developed between these N treatments with time. Growth of inoculated plants was more variable (CV = 38%) than that of plants dependent on soil N of fertilizer N. This variation in the growth of the inoculated plants was thus due to the large differences in the N2-fixing abilities than to intrinsic growth differences.